Study on the Influence of Rock Clip Production and Empty Hole Volume Effect of Upward Blind Shaft Blasting - Huang, Yonghui; Sun, Bo; Zhang, Zhiyu; Meng, Jiale; Zeng, Hua (Frontiers in Earth Science, 2022)
Cutting blasting is the principal construction method for roadway and shaft excavation, but the studies on the damage mechanism of cutting blasting affected by the volume effect of empty holes under high ground stress are not insufficient. During cutting blasting, different damage zones are formed. In this paper, combined with rock damage criterion and RHT constitutive function, the ranges of these damage zones are determined. The smooth particle hydrodynamics method is used to study the influence of high in-situ stress on rock blasting damage from the perspective of the number of empty holes and the production coefficient of rock clamp. The accuracy of the determined damage zone range is verified by supplemented field tests. The research results show that in the process of rock clamp production, the propagation of blasting stress wave is inhibited, especially the tensile stress wave which is more obvious inhibited. The empty holes reduce the inhibitory effect of rock clamp production. With the increase in the production coefficient of rock clip, the blasting damage radius is reduced by 39.7 %, 35.1 %, 30.5 %, 26.7 % and 22.9 % compared with the theoretical value, respectively, while its influence on the radius of crushing zone is small. The three-dimensional scanning results were used to inverse calculate the production coefficient of rock clip. The fitting degree between the numerical simulation and the field test scanning results is about 94.5 %, which proves the accuracy of the RHT constitutive parameters and the reliability of the determination range. The mathematical relationship between the production coefficient Kr for rock clip and the relative height H of the wellhead and the area Sc of the cross-section cavity is fitted based on the data of several field upward cutting blasting tests.